The Duality of Empowerment and Marginalization in Microtask Crowdsourcing: Giving Voice to the Less Powerful Through Value Sensitive Design1 - Deng, Xuefei (Nancy); Joshi, K. D.; Galliers, Robert D. (MIS Quarterly, 2016)
Crowdsourcing (CS) of micro tasks is a relatively new, open source work form enabled by information and communication technologies. While anecdotal evidence of its benefits abounds, our understanding of the phenomenon’s societal consequences remains limited. Drawing on value sensitive design (VSD), we explore microtask CS as perceived by crowd workers, revealing their values as a means of informing the design of CS platforms. Analyzing detailed narratives of 210 crowd workers participating in Amazon’s Mechanical Turk (MTurk), we uncover a set of nine values they share: access, autonomy, fairness, transparency, communication, security, accountability, making an impact, and dignity. We find that these values are implicated in four crowdsourcing structures: compensation, governance, technology, and microtask. Two contrasting perceptions—empowerment and marginalization—coexist, forming a duality of microtask CS. The study contributes to the CS and VSD literatures, heightens awareness of worker marginalization in microtask CS, and offers guidelines for improving CS practice. Specifically, we offer recommendations regarding the ethical use of crowd workers (including for academic research), and call for improving MTurk platform design for greater worker empowerment.